2023
DOI: 10.24976/discov.med.202335175.16
|View full text |Cite
|
Sign up to set email alerts
|

High Red Blood Cell Distribution Width to Platelet Ratio is an Independent Poor Prognostic Factor in Patients with Newly Diagnosed Multiple Myeloma

Abstract: Background:The red blood cell distribution width to platelet ratio (RPR) is an inflammatory marker that is a convenient and reliable prognostic indicator for several solid malignancies. However, the correlation between RPR and myeloma prognosis has not been reported. Therefore, this study aims to explore the correlation between RPR level and the prognosis of multiple myeloma (MM) patients. Methods: We retrospectively analyzed 145 newly diagnosed patients with MM. The receiver operating characteristic curve (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The RDW to platelet ratio (RPR) is a newly proposed composite parameter index that plays an important role in predicting the prognosis of many diseases. Studies have shown that the RPR in the peripheral blood is an independent risk factor affecting the prognosis of glioblastoma and acute pancreatitis, while an elevated RPR index suggests a poor prognosis for breast cancer and multiple myeloma [ 9 - 12 ]. However, research is lacking on the prognostic relevance of RPR for patients with newly diagnosed DLBCL.…”
Section: Introductionmentioning
confidence: 99%
“…The RDW to platelet ratio (RPR) is a newly proposed composite parameter index that plays an important role in predicting the prognosis of many diseases. Studies have shown that the RPR in the peripheral blood is an independent risk factor affecting the prognosis of glioblastoma and acute pancreatitis, while an elevated RPR index suggests a poor prognosis for breast cancer and multiple myeloma [ 9 - 12 ]. However, research is lacking on the prognostic relevance of RPR for patients with newly diagnosed DLBCL.…”
Section: Introductionmentioning
confidence: 99%